Factors Affecting the Quality of Life in Patients with Fibromyalgia - Nuri Çetin; Şeniz Akçay Yalbuzdağ; Mehmet Tuğrul Cabıoğlu; Nur Turhan (Archives of Rheumatology, 2009)
Objective: Fibromyalgia is a chronic musculoskeletal pain syndrome characterized by diffuse pain and specific painful tender points. This study was planned to gain a better understanding of the factors that may impact the quality of life of patients with fibromyalgia. Material and Methods: The study was carried out in the Physical Therapy and Rehabilitation outpatient clinic with 35 women with fibromyalgia and 20 healthy women with no current or past medical history as controls. The subjects were evaluated with digital palpation to test tender points, by algometric measurements to test pressure pain threshold, the Short-Form McGill Pain Questionnaire (SF-MPQ) scores to test pain severity, and the Fibromyalgia Impact Questionnaire (FIQ) to test quality of life. Results: The two groups were similar with respect to mean age, body mass index and education status. Algometric pressure pain thresholds of tender point sites were lower in patients with fibromyalgia than in healthy controls. In this patient group, there were linear relations between the number of tender points, duration of pain, SF-MPQ scores, and FIQ. There were also linear relations between duration of pain and SF-MPQ scores and the total number of tender points. Conclusion: In the patient group, all the pain measurements were significantly correlated with each other. The quality of life score was also significantly related to each of the pain parameters. (Turk J Rheumatol 2009; 24: 77-81)